Análise dos fatores de risco e formas de prevenção para minimizar os sintomas de depressão pós-parto - DIÓGENES, Sarah Laíssa Silveira (2024)
Postpartum depression (PPD) is considered a serious public health problem, being a condition totally related to the birth of the baby. It is a disease that needs care and special attention so that the psychic suffering that affects these women can be overcome. From a medical perspective, PPD is the result of major changes in hormone levels, in addition to genetic, obstetric and mother and baby health factors. This work aims to carry out a literature review based on the following guiding question: how to minimize the impact of postpartum depression? The databases used were BVS, SCIELO and Pubmed. Inclusion criteria: works published in full electronically and free, in the period from 2012 to 2022 that fit the theme. 15 articles were selected. The results showed that PPD has a multifactorial cause, however, there are some triggering risk factors, the most cited among the articles were financial difficulties, hormonal changes and lack of family and social support. The most cited forms of prevention were partner and family support, in addition to good assistance from the health team.